Implementasi Trigonometri Pada Tinggi Suatu Objek - Aulia, Virna; Aprilia, Maelani; Anastasya, Wanda; Mawariah, Mawariah; Panggabean, Ellis Mardiana (Cybernetics: Journal Educational Research and Social Studies, 2024)
Trigonometry is a branch of mathematics that studies the relationships between the sides and angles of triangles. In its applications, trigonometry plays a crucial role in various fields such as physics, engineering, architecture, and navigation. One prominent application of trigonometry is in determining the height of an object. This article discusses the application of trigonometry in measuring object heights using techniques like theodolites, laser rangefinders, and drones. Trigonometry enables precise measurements by utilizing elevation angles and distances, and it plays a critical role in maintaining accuracy in construction, navigation, and surveying.